Comparative evaluation of effectiveness of 2% lignocaine hydrochloride with 1.5% potassium chloride versus 2% lignocaine hydrochloride with adrenaline bitartrate versus 2% lignocaine hydrochloride as local anaesthetic for adult patients undergoing surgical extraction of impacted mandibular third molars: a randomized controlled clinical study - Kalra Rinku (EDP Sciences, 2021)
Background and objective: Administration of some additives with local anesthetics can prolong pain free period post-operatively, thereby reducing need for post-operative analgesics and improving patient comfort. Potassium chloride was found to increase duration and quality of anesthesia in various studies on brachial plexus blockade. This study was designed to evaluate and compare the effect of 2% lignocaine with 1.5% potassium chloride, 2% lignocaine with adrenaline and 2% lignocaine (plain) in pterygomandibular nerve blocks. Materials and methods: A triple blind randomized controlled study was conducted on 120 adults, aged 18–45 years in ASA-I category, requiring surgical extraction of impacted mandibular third molars. The subjects were divided equally into 3 groups randomly by computer generated sequence; Group 1: 2% lignocaine plus 1.5% solution of potassium chloride, group 2: 2% lignocaine with 1:80,000 adrenaline and group 3: 2% plain lignocaine. Onset, duration, depth (pain) of anesthesia, patient satisfaction, systolic and diastolic blood pressures, heart rate and oxygen saturation, were evaluated and compared. Results: Onset was shortest for group1 and longest for grp3, statistically highly significant difference between the 3 groups (p < 0.01). Statistically significant difference (p < 0.05) was found in duration of surgery, duration of analgesia and VAS scores between groups 1 & 3. Duration and depth of anesthesia were comparable for groups 1 & 2. There was no statistically significant difference seen for total amount of dose used, SBP, DBP, HR and SpO2 between the 3 groups (p > 0.05). Conclusion: Potassium chloride, a physiological salt is inert and causes no local/systemic adverse effects when injected with lignocaine in physiologically permissible amounts. The combination achieves satisfactory onset, duration, depth of anesthesia without altering hemodynamic variables. Hence, it may be considered as a safe and effective additive.